New Light on ‘Father’ Smith and the Organ of Christ Church, Dublin - Duncan, Cheryll (Journal of the Society for Musicology in Ireland, 2015)
According to received opinion, Bernard Smith never built the new organ that Christ Church, Dublin, commissioned from him in May 1694, and the contract was later awarded to his rival Renatus Harris; documents from the courts of Chancery and King’s Bench show that narrative to be only partially true. In 1697 William Moreton, Bishop of Kildare, instituted proceedings against Smith for breach of contract, from which it emerges that Smith actually built two organs for the cathedral. However, for various reasons, including Moreton’s dithering over stops, difficulties arranging delivery and transferring money, the cost and Harris’s meddling, both agreements ultimately foundered, leaving Smith with two unsold instruments. Great St Mary’s, Cambridge, took one of them, and St Michael’s, Barbados, probably the other. The documentation, comprising the lost contract and specification for Smith’s first Dublin organ, as well as depositions from Harris, Henry Aldrich and John Blow, illuminates a shadowy corner of Christ Church’s musical history.